Polymorphism of genes CAST, GH, GDF9 of sheep of the Dagestan mountain breed - A. A. Ozdemirov; L. N. Chizhova; A. A. Khozhokov; E. S. Surzhikova; G. D. Dogeev; S. Sh. Abdulmagomedov (Юг России: экология, развитие, 2021)
Aim. To study the polymorphism of the genes calpastatin (CAST), somatotropin (GH) and differential growth factor (GDF9) of sheep of the Dagestan mountain breed.Material and Methods. Studies on the genetic typing of Dagestan mountain sheep according to CAST, GH and GDF9 genes were carried out in conditions of distant pasture farming in the Republic of Dagestan by the Genetics and Breeding Laboratory of the Federal Agrarian Scientific Centre of the Republic of Dagestan, an accredited laboratory of immunogenetics and DNA technologies of the All-Russian Research Institute of Sheep and Goat Breeding and a branch of the North Caucasus Federal Scientific Agrarian Centre. These investigations were undertaken by the PCR-RFLP method (polymyrase chain reaction - restriction fragment length polymorphism) on a Tersik four-channel programmable thermal cycler from DNA-Technologia (Russia) using specific primers synthesized in the SYNTHOL research and production laboratory (Moscow).Results. Carrying out PCR-RFLP revealed breed-specific alleles with different frequency of occurrence, which was: in the locus of the CAST gene - allele CASTN - 0.03; allele CASTM - 0.97; at the GH gene locus - GHA allele - 100.0, GHB allele - 0; in the locus of the GDF9 gene - the GDF9A allele - 0.25, the GDF9G allele - 0.75, which determined the frequency of occurrence of the homo- and heterozygous genotypes: CASTNN, CASTMM and CASTNM - 93.0; 0 and 7.0%; GHAA, GHBB and GHAB - 100.0 and 0%; GDF9AA, GDF9GG and GDF9АG- 16.0, 66.0 and 19.0%, respectively.Conclusion. The regularity revealed can be considered as an ecological factor that optimizes the adaptive functions of the sheep's organism, on the one hand, an evolutionary selection process that contributes to the creation of a specific way of genetic structures in the population, on the other. The assumption is made that the information obtained can serve as the beginning of a more in-depth study of the unique gene pool of sheep of the Dagestan rock breed for its further improvement. Variants of genetic marker profiles of parental pairs are proposed for accumulation in breeding herds bred in different ecological-geographical zones and genotypes of carriers of selection-significant genetic structures.